A basis for inquiry into policy considerations for increasing the application of biophilic urbanism - Reeve, A.; Desha, C.; Hargroves, Charlie; Newman, Peter; Hargreaves, D. (Springer, 2013)
Urban design that harnesses natural features (such as green roofs and green walls) to improve design outcomes is gaining significant interest, particularly as there is growing evidence of links between human health and wellbeing, and contact with nature. The use of such natural features can provide many significant benefits, such as reduced urban heat island effects, reduced peak energy demand for building cooling, enhanced stormwater attenuation and management, and reduced air pollution and greenhouse gas emissions. The principle of harnessing natural features as functional design elements, particularly in buildings, is becoming known as ‘biophilic urbanism’. Given the potential for global application and benefits for cities from biophilic urbanism, and the growing number of successful examples of this, it is timely to develop enabling policies that help overcome current barriers to implementation. This paper describes a basis for inquiry into policy considerations related to increasing the application of biophilic urbanism that captures and integrates knowledge from lived experience around the world. The paper draws on research undertaken as part of the Sustainable Built Environment National Research Centre (SBEnrc) in Australia. The paper discusses the emergence of a qualitative, mixed-method approach that captures lived experiences and extends beyond the literature and documented journeys of international cities that have encouraged biophilic urbanism. Stakeholder workshops provide context and scope to research to ensure it is targeted, and a meta-narrative is developed to extract key learnings of relevance.